Predictors of Esophageal Varices and Risk of Variceal Bleeding in Patients of Liver Cirrhosis - Panta, Prabesh; Khadka, Dipendra; Basnet, Subhechhya; KC, Rupak; Khanal, Bibek; Shah, Gaurav Jung (Journal of Nepalgunj Medical College, 2022)
Introduction: Variceal bleeding from esophageal varices has high morbidity and mortality. There are invasive and non invasive methods by which risk of bleeding can be predicted. Upper Gastro-intestinal endoscopy is invasive, uncomfortable and expensive procedure though being the gold standard to screen Esophageal Varices (EV). Aims: To know the role of non-invasive markers for prediction of esophageal varices and variceal bleed with liver cirrhosis. Methods: A prospective hospital based study was carried in the Department of Internal Medicine, Nepalgunj Medical College, Kohalpur from October 2021 to March 2022. A total of 70 patients who met the inclusion criteria were enrolled. The non invasive markers were done and correlated with endoscopy. Results: Our study included 70 patients with liver cirrhosis. The mean age in our study was 63.1±8.346 years. During upper gastrointestinal endoscopy, esophageal varices was present in 46 (65.71%) patients. Child Turcot Pugh Score C (81.43%) was found in majority. Significant association was found between score C (P<0.05), thrombocytopenia, Model for End stage Liver Disease Score (P=0.017) and low albumin level with esophageal varices and variceal bleeding. Similarly, significant alcohol intake was associated with esophageal varices and variceal bleed. However, no association was found between age and esophageal varices. Conclusion: Child Turcot Pugh score, thrombocytopenia, low albumin level and Model for End stage Liver Disease along with significant alcohol intake correlated with presence of esophageal varices and can be considered as non invasive tools for screening of esophageal varices and variceal bleeding in cirrhosis.